Analysis of Cooperative Health Level at Mallomo Jaya Abadi Makassar Saving and Loan Cooperative - Mahmuda, Asriyani; Idris, Hariany; Nuraisyiah, Nuraisyiah (Invoice : Jurnal Ilmu Akuntansi, 2024)
The aim of this research is to analyze the health level of cooperatives in the Mallomo Jaya Abadi Makassar Savings and Loans Cooperative (KSP) for the 2020-2022 period. An assessment of the condition of the cooperative resulted in the predicates of being healthy, quite healthy, under supervision, and under special supervision. This research method is descriptive with a quantitative approach. The research data used are the financial reports of KSP Mallomo Jaya Abadi Makassar, especially the balance sheet and reports on the calculation of remaining operating results. The data collection techniques used were documentation and interviews. The data analysis technique is carried out by data reduction, data analysis based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and SMEs No. 06/Per/Dep.06/IV/2016, and drawing conclusions. The research results show that the health level of the Mallomo Jaya Abadi Makassar Savings and Loans Cooperative in 2020 is predicted to be 'Under Supervision', with a total score of 53.20. In 2021, the title was 'Under Supervision', with a total score of 58.20. In 2022, the title is 'Under Supervision' with a total score of 64.15. With a total score of 58.51, the predicate is 'Under Supervision'.